Integrating sustainable development into the curriculum - Sengupta, Enakshi; Blessinger, Patrick; Yamin, Taisir Subhi (Bingley, U.K. : Emerald Publishing Limited, 2020)
Creating a sustainable future is one of the biggest challenges that we face as a human race. This is often made even harder by the apathy of many towards the need for sustainability. Education will play a crucial role in finding a solution to the global climate crisis, by shaping future generations who are informed, enlightened and ready to take action. This book explores the value of institutions of higher education in leading the way on the topic of sustainability education by ensuring that it is well entrenched in the curriculum, as well as in everyday practice and lifestyles. This unique volume features authors from different parts of the world who narrate their own experience of integrating sustainability into their curriculum, and teaching sustainability to students. By exploring the idea that education and sustainability should be seen as intrinsically linked if we are to see global change, this important text will prove invaluable for leaders, scholars and policy specialists in higher education.
PART I: IN PRACTICE Introduction to integrating sustainability into curriculum / Enakshi Sengupta, Patrick Blessinger and Taisir Subhi Yamin -- Chapter 1: Integrating sustainable development into healthcare curriculum / Russell Gurbutt and Dawne Gurbutt -- Chapter 2: Embedding sustainable development in the curricula - learning about sustainable development as a means to develop self awareness / Louise Manning and Luis Kluwe de Aguiar -- Chapter 3: A comparative analysis of approaches to integrating sustainability into the curriculum at a university in a small island developing state in the Carribean / Alana Griffith and Winston Moore -- Chapter 4: Integrating sustainable development into the curriculum - a case study on the developing of sustainability competencies in industrial design students at a bachelor level in Mexico / Martha Elena Núñez López, Robert Huddleston, Roberto Pablo Martínez Lozano PART II: INNOVATIVE APPROACHES -- Chapter 5: Programs, workshops, resources and other supports for post secondary sustainability educators / Alice Cassidy, Yona Sipos and Sarah Nyrose -- Chapter 6: Hortus In Urbe: Building a sustainable development curriculum in Chicago / Euan Hague, Howard Rosing and Joesph P. Schwieterman -- Chapter 7: An interdisciplinary teaching module on the global clothing industry: lessons from working across four disciplines and two universities / Niki Harré, Anis Azizi, Penny Brothers, Ties Coomber, Ellinor King, Andrea Michelle Mead, Sarah Saeckel, Manuel Valle, Samantha Zi Lin Yeo, Yulun (Darren) Zhang -- Chapter 8: Integrating sustainability into a freshman -engineering course through an institute - level initiative: a teaching -learning model with authentic activity and context / Raghu Pucha, Kata Dosa, Sunni Newton, Meltem Alemdar, Ruthie Yow and Jennifer Hirsch -- Chapter 9: Integrating sustainable development into the curriculum: enacting 'scalar shifting' in esd competencies / Paul Benneworth, Renze Kolster, Martin Stienstra, Laura Franco-Garcia and Ben Jongbloed.
Includes indexes.
Includes bibliographical references.
Print version record.
Keywords: Education, Higher -- Curricula -- United States; Sustainability -- Study and teaching -- United States; Education -- Curricula; Curriculum planning & development